Pathways and cost-effectiveness of routine lung cancer inpatient care in rural Anhui, China: a retrospective cohort study protocol. Issue 2 (20th February 2018) - Shen, XingRong; Diao, MengJie; Lu, ManMan; Feng, Rui; Zhang, PanPan; Jiang, Tao; Wang, DeBin
Abstract : Introduction: Routine inpatient care (RIC) for patients with cancer forms various pathways of clinical procedures. Although most individual procedures comprising the pathways have been tested via clinical trials, little is known about the collective cost and effectiveness of the pathways as a whole. This study aims at exploring RIC pathways for patients with lung cancer from rural Anhui, China, and their determinants and economic impacts. Methods and analysis: The study adopts a retrospective cohort design and proceeds in five steps. Step 1 defines the four main categories of study variables, including clinical procedures, direct cost and effectiveness of procedures, and factors affecting use of these procedures and their cost and effectiveness. Step 2 selects a cohort of 5000 patients with lung cancer diagnosed between 1 July 2015 and 30 June 2016 from rural Anhui by clustered random sampling. Step 3 retrieves the records of all the inpatient care episodes due to lung cancer and extracts data about RIC procedures, proximate variables (eg, Karnofsky Performance Status, Lung Function Score) of patient outcomes and related factors (eg, stage of cancer, age, gender), by two independent clinician researchers using a web-based form. Step 4 estimates the direct cost of each of the RIC procedures using micro-costing and collects data about ultimate patient outcomes (survival and progression-free survival) through a follow-up survey of patients and/or their close relatives. Step 5 analyses the data collected and explores pathways of RIC procedures and their relations with patient outcomes, costs, cost:effect ratios, and a whole range of clinical and sociodemographic factors using multivariate regression and path models. Ethics and dissemination: The study protocol has been approved by an authorised ethics committee of Anhui Medical University (reference number: 20170312). Findings from the study will be disseminated through conventional academic routes such as peer-reviewed publications and presentations at regional, national and international conferences. Trial registration number: ISRCTN25595562 .